IOT Implemented Smart Aquaponics System Using Arduino with Fuzzy - Vijayan, Vinodh P; Joseph, Neena; Kurian, Simy Mary; Kurian, Simy Mary (International Journal of Computer Sciences and Engineering, 2025)
Aquaponics is an emerging region in food manufacturing technique which combines traditional hydroponics with aquaculture in a symbiotic surroundings that enables a sustainable machine with essential input as all of the water and nutrients inside are re-circulated in order to develop terrestrial plant life and aquatic lifestyles. When aquaponics gadget meets with technology it appears to produce some first rate outputs which makes it green and productive generation. In Iot Based Smart Aquaponics System with Fuzzy Logic, we take specific readings regarding the pH stage, temperature, moisture content and the extent of the water by using using distinctive sensors. Readings from every of these sensors are stored in the server for destiny use. Also these values are utilized by the bushy controller which controls the overall working of the system in drastic condition. Iot removes the gap between the physical world and digital international. In order to introduce technologies to the conventional aquaponics machine, we use of Arduino, Fuzzy controller and Internet of Things